2022
DOI: 10.1155/2022/9957604
|View full text |Cite
|
Sign up to set email alerts
|

A Novel‐Defined Necroptosis‐Related miRNA Signature for Forecasting the Prognosis of Low‐Grade Glioma

Abstract: Background. Increasing evidence has shown that necroptosis has enormous significance in the generation and deterioration of cancer, and miRNA molecular markers involved in necroptosis in low-grade gliomas (LGGs) have not been thoroughly reported. Methods. Using the miRNA data of 512 samples from The Cancer Genome Atlas (TCGA), 689 miRNAs from LGG samples were split into high immunity score and low immunity score groups for analysis. The differential miRNAs related to necroptosis were analyzed by univariate Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…We then used the same procedure to screen the upstream lncRNA of hsa-miR-7-5p. Previous studies revealed that the gene hsa-miR-7-5p could be useful for necroptosis and that it is expressed more frequently in neuroendocrine tumors 31,32 . MIR29B2CHG was shown to be downregulated www.nature.com/scientificreports/ in BRCA tissues, and knocking down its predicted promoter increased BRCA cell proliferation, migration, and invasion 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We then used the same procedure to screen the upstream lncRNA of hsa-miR-7-5p. Previous studies revealed that the gene hsa-miR-7-5p could be useful for necroptosis and that it is expressed more frequently in neuroendocrine tumors 31,32 . MIR29B2CHG was shown to be downregulated www.nature.com/scientificreports/ in BRCA tissues, and knocking down its predicted promoter increased BRCA cell proliferation, migration, and invasion 33 .…”
Section: Discussionmentioning
confidence: 99%